An Analysis of Barrier Factors in Teaching and Learning English at the Ninth Grade Student of SMP YKP Pertamina Jambi - Nur Kholis; Suyadi Suyadi; Siti Aisyah (JELT: Journal of English Language Teaching, 2021)
This research was aimed to find out the barrier factors in teaching and learning English at the ninth grade students of SMP YKP Pertamina Jambi. The research methodology of this study was qualitative research with random sampling. The researcher conducted at ninth grade students in SMP YKP Pertamina Jambi. The subject of this research is 1 teacher and 7 students, by using online interview with research instrument, technique of data collecting, and technique of data analysis. Overall, the result of this research showed barrier factors in teaching and learning English in SMP YKP Pertamina Jambi. Finding from this research shows that there are barrier factors when teaching and learning English, and factors that most influence students when learning English. Hence, it can be concluded that there was a barrier factor which was the teacher's mistake when learning English and the most dominant factor experienced by students was family factors that could affect in learning.Keywords: Barrier factors, teaching, learning process.